Government Trade Promotion Agencies : Strategies for Enhancing Global Market Access - Vasylenko, Yelyzaveta; Shymanska, Kateryna; Mazánková, Zuzana; Vysoká škola ekonomická v Praze. Fakulta mezinárodních vztahů (2024)
This thesis examines the role and key functions of GTPAs, their global best practices in trade promotion and their overall impact on economic growth. In addition, it is worth considering the main barriers these countries face when implementing trade agreements and GTPAs. Examine how these mechanisms impact the economic development of countries and what examples of successful application of these approaches can be identified.
Vedoucí práce: Kateryna Shymanska
Bakalářská práce (Bc.)—Vysoká škola ekonomická v Praze. Fakulta mezinárodních vztahů, 2025
Obsahuje bibliografii
Textový (vysokoškolská kvalifikační práce)
Rok obhajoby 2025
Způsob přístupu: Internet
Keywords: international business [obor bakal. práce]; bakalářské práce; bachelor's theses